The effect of multimedia use on the teaching and learning of Social Sciences at tertiary level: A case study (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Instructors in higher education are under pressure to provide their students with more effective and efficient learning environments and educationalexperiences. Instructional systems and educational technology have been receiving great attention from educators in order to enhance students’ learning.Educational technologies such as multimedia presentations are becoming commonplace. The aim of the research reported in this article was to establishwhich multimedia combinations are best for the teaching and learning of Social Sciences content. A quasi-experimental research design was usedto establish how exposure to different multimedia combinations on digital videodisc may affect the achievement of pre-service teachers. The results of thestudy indicate that when using various multimedia combinations, the unique nature of Social Sciences can be addressed effectively.
Keywords: History Education; Geography education multimedia; Social Sciences education; Teaching and learning; Tertiary/higher education; Educational technology integration